2011
DOI: 10.1097/qai.0b013e31822d4063
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Antiretroviral Therapy Versus Zidovudine for Prevention of Mother-to-Child Transmission in a Programmatic Setting, Botswana

Abstract: Few studies have compared the programmatic effectiveness of the recommended strategies of antenatal highly-active antiretroviral therapy (HAART) and zidovudine for prevention of mother-to-child transmission (MTCT). We prospectively followed infants (93% formula-fed) whose mothers who took either HAART (258 infants) or zidovudine (170 infants) during pregnancy in the Botswana national program. Overall, 10 infants (2.5%) acquired HIV— 9 infants in the zidovudine group (5.5%, 95%CI 2.6-10.2%) and 1 infant in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…However, more information on the safety and effectiveness of the preventive regimens can help in defining optimized strategies. In our study maternal ART administration was significantly beneficial for women’s health (with a very low mortality rate) and highly effective, with a transmission rate similar to other observational and randomized studies [2,13,14]. Although the very limited number of infections did not allow us to establish a significant correlation between one or more factors and the overall risk of transmission, some of our findings were intriguing.…”
Section: Discussionsupporting
confidence: 64%
“…However, more information on the safety and effectiveness of the preventive regimens can help in defining optimized strategies. In our study maternal ART administration was significantly beneficial for women’s health (with a very low mortality rate) and highly effective, with a transmission rate similar to other observational and randomized studies [2,13,14]. Although the very limited number of infections did not allow us to establish a significant correlation between one or more factors and the overall risk of transmission, some of our findings were intriguing.…”
Section: Discussionsupporting
confidence: 64%
“…However, with maternal highly active antiretroviral therapy (HAART), less than 2% of infants acquire HIV infection. [3][5] With improved access to maternal HAART during pregnancy and breastfeeding, [6] the recommendation to provide empiric cotrimoxazole prophylaxis for all HIV-exposed infants has been questioned. [7].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment as prevention also has been examined in maternal to child transmission with early studies showing reduction of maternal to child transmission from 20% to <2% [89]. A recent study from Botswana showed 2.5% of infants born to mothers receiving zidovudine were HIVinfected compared to 0.4% of infants born to mothers on combination antiretroviral therapy (cART, previously known as highly active antiretroviral therapy or HAART) [90]. This data further solidifies the need for earlier diagnosis of HIV infected individuals and broader treatment of HIV-infected individuals to prevent new HIV infections.…”
Section: Treatment As Preventionmentioning
confidence: 97%